LAURIAN SOMEȘAN ÎNTRE ZENIT ȘI NADIR, ADICĂ ÎNTRE EMULAȚIE IDENTITARĂ – ÎMPLINIRE PROFESIONALĂ ȘI EPURARE-MARGINALIZARE ÎN PERIOADA ALTERITĂȚII PROLETCULTISTE - Alexandru PĂCURAR (Studia Universitatis Babeş-Bolyai: Geographia, 2020)
Professor Laurian Someșan, a geographer formed under the leadership of George Vâlsan, the one who laid the foundations of the Cluj School of Geography, experienced a sinuous professional development due to the hardship of the times, namely the fact that Romania was assigned to the sphere of Soviet influence. Getting himself noticed as early as on the desks of the faculty by the scholar George Vâlsan, Laurian Someșan became, in the third year of college, a preparatory assistant at the Institute of Geography of the “King Ferdinand I” University of Cluj, where he advanced in his career to the teaching degree of Senior Lecturer. Stopped in his professional ascent for obscure reasons, Laurian Someșan was transferred to the Academy of High Commercial and Industrial Studies of Cluj which was in its refuge at Brașov, due to the cession of the north-west Transylvania, to which Romania had been forced. There he reached the top of the professional hierarchy due to his won merits; he also had the position of Rector of this Academy (1947-1948). After the abusive abolition of the monarchy, Professor Laurian Someșan gradually met the avatars of marginalization, his removal from higher education culminating with the prison regime and forced labour that was imposed to him (15 August 1952-April 1954) by the oppressive regime. The author tries to explain the resorts that have been at the basis of these accumulated abuses.